2013
DOI: 10.1007/s00595-013-0719-x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of the postoperative recurrence of lung cancer in octogenarians

Abstract: Antitumor treatment of postoperative recurrent lung cancer in octogenarians may not always improve the survival rate. However, carefully selecting patients for intensive therapy, such as those with a good performance status, may lead to longer survival rates after postoperative recurrence in octogenarians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Recently, Yasuda et al reported the treatment outcomes of postoperative recurrence of lung cancer in octogenarians [24]. In that study, the median survival time after recurrence was 538 days in the intensive treatment groups (n = 6), 305 days in the palliative treatment group (n = 14) and 155 days in the supportive care only group (n = 17) [24]. The present results for aggressive treatment are considered to be favorable in comparison with these findings.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Recently, Yasuda et al reported the treatment outcomes of postoperative recurrence of lung cancer in octogenarians [24]. In that study, the median survival time after recurrence was 538 days in the intensive treatment groups (n = 6), 305 days in the palliative treatment group (n = 14) and 155 days in the supportive care only group (n = 17) [24]. The present results for aggressive treatment are considered to be favorable in comparison with these findings.…”
Section: Discussionsupporting
confidence: 47%
“…The frequency of treatmentrelated death was also not significant between the two groups. Recently, Yasuda et al reported the treatment outcomes of postoperative recurrence of lung cancer in octogenarians [24]. In that study, the median survival time after recurrence was 538 days in the intensive treatment groups (n = 6), 305 days in the palliative treatment group (n = 14) and 155 days in the supportive care only group (n = 17) [24].…”
Section: Discussionmentioning
confidence: 97%
“…This critical knowledge gap is largely because cancer registries do not report recurrence or subsequent treatment [19, 20]. This leaves researchers to investigate treatment for recurrent disease in small, single institution studies [3, 21, 22]. For example, active cancer-directed treatment for postoperative NSCLC recurrence ranged from 54% among octogenarians in one Japanese institution [21] to 69% of adult patients in one U.S. institution [3].…”
Section: Introductionmentioning
confidence: 99%
“…This leaves researchers to investigate treatment for recurrent disease in small, single institution studies [3, 21, 22]. For example, active cancer-directed treatment for postoperative NSCLC recurrence ranged from 54% among octogenarians in one Japanese institution [21] to 69% of adult patients in one U.S. institution [3]. Neither study examined factors associated with receipt of treatment for postoperative recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…EGFR-TKI is thought to be useful anti-cancer drug with little burden especially in elderly patient. 20) The role of chemotherapy and radiotherapy in the treatment of lung cancer in octogenarians should be elucidated in the future. Five-year OS was 57.5% in this study which was almost the same survival rate compared to previous reviews.…”
Section: Discussionmentioning
confidence: 99%